Dose Distribution 6 MV of X-Ray Photon Beam over Cerium Oxide Nanoparticles Solution - Iis Nurhasanah; Hella Arofah; Agus Subagio; Eko Hidayanto; Tri Windarti (Journal of Physics and Its Applications, 2020)
CeO2 nanoparticles are biomaterial that demonstrate potential as antioxidant and radioprotector for medical application. In this study, the radioprotector properties of CeO2 nanoparticles was evaluated by measuring absorbed dose of X-ray radiation. CeO2 nanoparticles were synthesized by precipitation and characterized using UV-Vis and FTIR spectrometers. CeO2 nanoparticle solution was prepared with various concentrations from 0.005 mg/mL to 0.06 mg/mL. The solution was exposed to 6 MV X-ray photon beam from medical linear acceleration with a source-to-surface distance of 100 cm and radiation dose of 2 Gy. The absorbed dose of X-ray by CeO2 nanoparticle solution was measured by an ion chamber detector. The absorbance peak at 301 nm observed in UV-Vis spectrum and absorbance peak at 854 and 492 cm-1 in the FTIR spectrum confirmed the formation of CeO2 nanoparticles. Radiation dose measurement exhibited dose reduction of CeO2 nanoparticles solution depend on concentration. CeO2 nanoparticle solution with concentration higher than 0.04 mg/mL showed potential application for radioprotector 6 MV of X-ray photon beam.